A Higher than Expected Incidence of Factor VIII Inhibitors in Multitransfused Haemophilia A Patients Treated with an Intermediate Purity Pasteurized Factor VIII Concentrate - Peerlinck, Kathelijne; Arnout, Jef; Gilles, Jean Guy; Saint-Remy, Jean-Marie; Vermylen, Jos (Thrombosis and Haemostasis, 1993)
In May 1990, 218 patients with haemophilia A regularly attending the Leuven Haemophilia Center were randomly assigned to a group receiving either of two newly introduced factor VIII concentrates: factor VIII-P, an intermediate purity pasteurized concentrate, or factor VIII-SD, a high purity concentrate treated with solvent-detergent for viral inactivation.Patients were followed from May 1990 until October 1991. Between August 1991 and October 1991 a clinically important factor VIII inhibitor was detected in five out of the 109 patients receiving factor VIII-P while none of the 109 patients receiving factor VIII-SD developed such antibodies. All patients acquiring an inhibitor had previously been clinically tolerant to transfused factor VIII with 200 to more than 1,000 days of exposure to factor VIII prior to May 1990. Patients with inhibitors were transfused daily with 30 U factor VIII-SD per kg body weight, which was associated with a gradual decline of the inhibitor level. In all patients the antibodies were relatively slow-acting and predominantly directed towards the light chain of factor VIII.This study demonstrates a higher than expected incidence of factor VIII inhibitors associated with the use of a specific factor VIII concentrate in multitransfused haemophilia A patients. It indicates the usefulness of evaluating newly introduced concentrates in prospective, randomized trials.